Serum microRNA 143 as a potential biomarker for the diagnosis of hepatitis C virus-related hepatocellular carcinoma - Ahmed M El-Gohary; Ahmed E Zeid; Mohamed E Ibrahim; Fatma I Dewedar; Essam A Elzoheiry (SpringerOpen, 2019)
Background Hepatocellular carcinoma (HCC) is the fifth most frequently diagnosed cancer worldwide. Early recognition of the onset of HCC would help to select more effective therapies for patients leading to a better prognosis and life span. So, the development of effective markers for the diagnosis of HCC could have an impact on HCC-related cancer mortality. MicroRNAs (miRNAs) are reported as a group of small noncoding RNAs that can function as endogenous RNA interference to regulate the expression of targeted genes. Aim To study serum miR-143 expression level in patients with hepatitis C virus (HCV)-related HCC. Patients and methods The present study was conducted on 60 participants classified into group A: 30 patients with HCV-related cirrhosis with HCC; group B: 15 patients with HCV-related cirrhosis without HCC; and group C: healthy participants as control. Expression of miR-143 in the serum of all participants was obtained in all groups. Total serum RNA was extracted with small RNA enrichment followed by reverse transcription real-time PCR. Expression of miR-143 in the serum of all participants was obtained using the comparative cycle threshold method (2-ΔΔCT) after normalization for the expression of Syn-cel-miR-39 mi script miRNA mimic as control. MiR-143 expression levels were then compared in different groups. Results The mean serum miR-143 levels were significantly higher in cirrhotic patients without and with HCC than in healthy participants (1.69±0.64, 13.0±6.23 vs. 0.56±0.29, P˂0.001, respectively) and in patients with HCC than in patients without HCC (P<0.001). The mean serum miR-143 levels were significantly higher in cirrhotic patients with HCC Barcelona Clinic Liver Cancer stage D than stage B (19.91±2.40, 13.41±1.80, P˂0.001, respectively) and in stage B compared with stage A (13.41±1.80, 5.68±1.86, P<0.001, respectively). Conclusion The significantly higher serum level of miR-143 in cirrhotic patients with HCC compared with those without and to normal participants may suggest its role in hepatocarcinogenesis and may have a value as a potential biomarker for early diagnosis of HCV- related HCC.